Colitis reduces active social engagement in mice and is ameliorated by supplementation with human microbiota members - D. Garrett Brown; Michaela Murphy; Roberto Cadeddu; Rickesha Bell; Allison M. Weis; Tyson R. Chiaro; Kendra A. Klag; Jubel Morgan; Hilary Coon; W. Zac Stephens; Marco Bortolato; June L. Round (2024)
Abstract Multiple neurological disorders are associated with gastrointestinal (GI) symptoms, including autism spectrum disorder (ASD). However, it is unclear whether GI distress itself can modify aspects of behavior. Here, we show that mice that experience repeated colitis have impaired active social engagement, as measured by interactions with a foreign mouse, even though signs of colitis were no longer present. We then tested the hypothesis that individuals with ASD harbor a microbiota that might differentially influence GI health by performing microbiota transplantation studies into male germfree animals, followed by induction of colitis. Animals that harbor a microbiota from ASD individuals have worsened gut phenotypes when compared to animals colonized with microbiotas from familial neurotypical (NT) controls. We identify the enrichment of Blautia species in all familial NT controls and observe an association between elevated abundance of Bacteroides uniformis and reductions in intestinal injury. Oral treatment with either of these microbes reduces colon injury in mice. Finally, provision of a Blautia isolate from a NT control ameliorates gut injury-associated active social engagement in mice. Collectively, our data demonstrate that past intestinal distress is associated with changes in active social behavior in mice that can be ameliorated by supplementation of members of the human microbiota.